Congenital Lumbar Hernia with VACTERL Anomaly: A Rare Presentation - Mohd. Aamir; Harish Punia; Kamal Nayan Rattan; Aditi Singh; Pooja Tripathi (JCDR Research and Publications Pvt. Ltd., 2015)
Congenital lumbar hernia also known as Lumbocostovertebral syndrome comprises various skeletal abnormalities like hemivertebrae, rib defects, abdominal wall anomalies and abdominal muscle hypoplasia. In this case report we describe a rare case of a neonate presenting with an unusually high number of congenital anomalies including lumbar hernia, high anorectal malformation, left inguinal hernia, thoracolumbar meningomyelocele, hemivertebrae and right crossed fused ectopic kidney. We intend to describe this rare association and a brief review of literature.